2016
DOI: 10.1021/acs.nanolett.5b04300
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing a Quantum Design Approach for Making Low-Loss Superlenses

Abstract: Recently, so-called "superlenses", made from metamaterials that are structured on a length scale much less than an optical wavelength, have shown impressive diffraction-beating image resolution, but they use materials with negative dielectric responses, and they absorb much of the light in a way that seriously degrades both the resolution and brightness of the image. Here we demonstrate an alternative "quantum metamaterials" (QM) approach that uses materials structured at the nanoscale, i.e., comparable to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This results, for instance, in supporting high‐ k states since it was demonstrated that bulk propagating waves with large wave vectors in periodic multilayer HMMs originate from coupling of surface plasmon polaritons (SPPs) in the individual metal layers . Therefore, HMMs have been intensively studied in the context of negative refraction, far‐field subwavelength imaging, plasmon polaritons, and spontaneous emission rate alterations . However, while the HMM's large PDOS was shown to increase the radiative decay rate of fluorescent emitters, it remains unclear how the crossover between plasmonic, HD, and interference effects occurs and what parameter would be best used to formalize possible crossovers from one dominant regime to another.…”
Section: Introductionmentioning
confidence: 89%
“…This results, for instance, in supporting high‐ k states since it was demonstrated that bulk propagating waves with large wave vectors in periodic multilayer HMMs originate from coupling of surface plasmon polaritons (SPPs) in the individual metal layers . Therefore, HMMs have been intensively studied in the context of negative refraction, far‐field subwavelength imaging, plasmon polaritons, and spontaneous emission rate alterations . However, while the HMM's large PDOS was shown to increase the radiative decay rate of fluorescent emitters, it remains unclear how the crossover between plasmonic, HD, and interference effects occurs and what parameter would be best used to formalize possible crossovers from one dominant regime to another.…”
Section: Introductionmentioning
confidence: 89%
“…These metal–supported surface plasmons (SPs) alter the phases and amplitudes of EM excitations, providing a means to manipulate light at the nanometer scale, trap, and manipulate their enhanced local fields within designer nanocavities, or leverage their decay into hot carriers to drive new chemical and physical phenomena. SPs have found applications in energy harvesting, , photocatalysis, sensors, and engineered metamaterials, where they can display negative refractive index, enable flat optics, and provide subwavelength resolution imaging capability. The confinement of quantum emitters to nanometer-scale plasmonic cavities can lead to light-matter interactions in the strong coupling limit, fast optical switching, and all-optical transistors …”
Section: Introductionmentioning
confidence: 99%
“…With a well-developed semiconductor industry, semiconductors have broader and more direct applications in on-chip plasmonic optoelectronic applications such as super-lens, lasing, and sensing. [12][13][14] Notably, small bandgap materials deserve more attention because their electron transport properties could be readily tuned due to the small effective mass and high electron mobility. [15,16] InSb is an excellent small bandgap semiconductor.…”
Section: Introductionmentioning
confidence: 99%